2014
DOI: 10.1371/journal.pone.0096461
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Age-Related and Anterior Polar Cataracts in a Korean Population

Abstract: ObjectiveTo investigate the potential risk factors associated with nuclear, cortical, posterior subcapsular, and anterior polar cataracts (APC) in the Korean population.Research Design and MethodsThis was a population-based, cross-sectional study of 7992 adults (over 40 years of age) from the data of the fourth annual Korea National Health and Nutrition Examination Survey, performed from 2007 to 2009. The presence of lens opacity was examined by slit-lamp biomicroscopy and evaluated according to LOCS II standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…Previous studies have showed that ARC occurs more common in female than male[ 3 , 37 , 38 , 39 , 40 ]. In our present study, female gender was also found as independent risk factors for cortical and nuclear cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have showed that ARC occurs more common in female than male[ 3 , 37 , 38 , 39 , 40 ]. In our present study, female gender was also found as independent risk factors for cortical and nuclear cataract.…”
Section: Discussionmentioning
confidence: 99%
“…A structured eye examination was performed using a slit-lamp (Haag-Streit model BQ-900; Haag-Streit AG, Koeniz, Switzerland) to evaluate the participants’ cataract status [28]. The standard Lens Opacities Classification System III (LOCS III) was used to categorize the type of cataract.…”
Section: Methodsmentioning
confidence: 99%
“…[22][23][24][25][26] Briefly, ophthalmology residents performed comprehensive slitlamp eye examinations using a BQ 900 slitlamp (Haag-Streit AG). The standard Lens Opacities Classification Systems III (LOCS III) was used to assess cataracts.…”
Section: Age-related Cataract Assessmentsmentioning
confidence: 99%